2022
DOI: 10.3390/molecules27207097
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) Complex Containing 4-Fluorophenoxyacetic Acid Hydrazide and 1,10-Phenanthroline: A Prostate Cancer Cell-Selective and Low-Toxic Copper(II) Compound

Abstract: Prostate Cancer (PCa) is the second leading cause of cancer-related deaths among men worldwide. The treatment of advanced cases is based on chemotherapy, which lacks specificity and efficacy, due to severe side effects and resistance to the traditional drugs. Copper complexes have shown antitumoral efficacy and low toxicity, being considered a promising class of metal-based drugs for the treatment of malignant neoplasms. Thus, the present study aimed to evaluate the cellular effects of a copper(II) complex wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…In addition to common copper chelators, various new drugs based on copper chelation have been developed and have been shown to be effective in preliminary studies. [75][76][77] Chen et al synthesized a nanoparticle that combined copper with diethyldithiocarbamate, an active metabolic component of DSF. The nanoparticle exhibited good anticancer activity against paclitaxel-resistant PC cells 61 (Figure 4C).…”
Section: Copper Nanoparticlesmentioning
confidence: 99%
“…In addition to common copper chelators, various new drugs based on copper chelation have been developed and have been shown to be effective in preliminary studies. [75][76][77] Chen et al synthesized a nanoparticle that combined copper with diethyldithiocarbamate, an active metabolic component of DSF. The nanoparticle exhibited good anticancer activity against paclitaxel-resistant PC cells 61 (Figure 4C).…”
Section: Copper Nanoparticlesmentioning
confidence: 99%
“…The copper complex [Cu(4-FH)(phen)(ClO 4 ) 2 ] (DRI-12) was previously evaluated for its physicochemical properties, cytotoxicity in tumours [21], selectivity and non-mutagenicity in tests with Drosophila melanogaster (in press) [22], as well as its antimycobacterial activity [20]. These studies revealed that DRI-12 has high potency and low toxicity, which makes it a promising compound to fight cancer and microorganisms.…”
Section: Copper Complex Effectmentioning
confidence: 99%
“…Moreover, copper is an essential trace element with importance for the functioning of several enzymes involved in energy metabolism, respiration and DNA synthesis in the cell, which make it very attractive for the development of safe and effective drugs [17][18][19]. Thus, DRI-12 was recently prepared [20] as a selective copper (II) complex containing 4-fluorophenoxyacetic acid hydrazide and 1,10-phenanthroline, and it has shown DNA-cleaving and pro-apoptotic properties in cancer cells, as well as selectivity and non-mutagenicity in tests with Drosophila melanogaster [21,22].…”
Section: Introductionmentioning
confidence: 99%